Pelatihan JULEHA: Penyembelihan Halal yang Syar'i dan Higienis - Fuadi; Falahuddin; Hafizh, Muhammad; Munardi; Arliansyah; Hanif (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities were conducted in Lhokseumawe City, focusing on meat traders and targeting both youth and the general public. The primary objective of this community empowerment initiative was to enhance understanding and provide assistance in halal slaughtering through training and certification for halal slaughterers (juleha) among market meat traders in Lhokseumawe. This effort aims to ensure the sustainability and development of halal slaughtering practices in the future. The training program was designed as an intensive and continuous educational activity, accompanied by experts from the PKM Unimal team and MPU-SJPH Aceh. The implementation method comprised three main stages: (1) Preparation, which included forming a field implementation team, conducting outreach to the community and meat traders, recruiting expert tutors in halal slaughtering, and coordinating with the implementation team; (2) Execution, which involved delivering material on halal slaughtering techniques, constructing appropriate slaughtering facilities, procuring necessary equipment, and carrying out the slaughtering process; and (3) Evaluation, as the final stage, where outcomes were assessed to improve future activities. The program is also designed to be sustainable through independent funding. Evaluation was conducted by comparing the conditions of participants before and after the mentoring process, using interviews and observation.